2019
DOI: 10.1097/ta.0000000000002161
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic human immunodeficiency virus–infected patients have poorer outcomes following emergency general surgery: A study of the nationwide inpatient sample

Abstract: BACKGROUND The impact of human immunodeficiency virus (HIV) infection on outcomes following common emergency general surgery procedures has not been evaluated since the widespread introduction of highly active antiretroviral therapy. METHODS A retrospective cohort study was conducted using the Nationwide Inpatient Sample. Records of patients who underwent laparoscopic or open appendectomy, cholecystectomy, or colon resection after emergency admission fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Sandler et al analyzed a large series of patients undergoing emergency surgery [ 138 ]. Their propensity score analysis compared HIV-positive patients without AIDS, AIDS patients, and HIV-negative patients.…”
Section: Patients With Hiv/aidsmentioning
confidence: 99%
“…Sandler et al analyzed a large series of patients undergoing emergency surgery [ 138 ]. Their propensity score analysis compared HIV-positive patients without AIDS, AIDS patients, and HIV-negative patients.…”
Section: Patients With Hiv/aidsmentioning
confidence: 99%
“…In addition, they had significantly increased odds of postoperative complications, including sepsis, septic shock, pneumonia, urinary tract infection, acute renal failure, and need for transfusion. This was not true of the asymptomatic HIV+ surgical patients in the same study . Less is known about LMIC and especially about head and neck surgery in the surgical mission setting.…”
Section: Introductionmentioning
confidence: 75%
“…Some studies have shown that the postoperative complication rate of patients with well-controlled HIV infection is comparable to that of HIV (−) patients [ 21 24 ]. However, HIV infection is generally considered a surgical risk in terms of higher postoperative complications and longer hospital stays [ 3 ]. From the perspective of predicting the postoperative course, some studies have found that a low CD4 + lymphocyte count, especially < 200 cells/μL, was associated with a significant increase in postoperative complications after surgical intervention, including abdominal surgery [ 14 , 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%